PENGARUH KONFLIK PERAN GANDA DAN STRESS KERJA TERHADAP KINERJA DOSEN WANITA SE PTKIN PROVINSI - Seprianto, Seprianto; Daflaini, Daflaini (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to determine whether there is an influence of Work Family conflict and work stress on the performance of lecturers at Stete Islamic Institute of Kerinci and State Islamic University of Sulthan Thaha Saefuddin Jambi. The sample of this study were female lecturers at the Faculty of Education and Teacher Training at State Islamic Institute of Kerinci and State Islamic University of Sulthan Thaha Saifuddin Jambi which consisted of 98 lectures, and this was used total sampling technique. The data collection techniques used a questionnaire. Then, the Data was analysed by using SPSS 21 program which used multiple linear analysis. The results of this study showed that (1) there is a positive and significant influence between Work Family conflict on the performance of female lecturers at State Islamic Institute of Kerinci and State Islamic University of Sulthan Thaha Saefuddin Jambi with a significance value of 0.000 0.05, (3) there is a Work Family conflict and work stress has a positive and significant influence on the performance of female lecturers at State Islamic Institute of Kerinci and State Islamic University of Sulthan Thaha Saifuddin Jambi with a significance value of 0.000 < 0.05.